2021
DOI: 10.1155/2021/5598291
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biocompatible Herbal Extract‐Loaded Hydrogel for Acne Treatment and Repair

Abstract: A novel herbal extract-loaded gel containing several biofunctional extracts, including green tea, Zingiber officinale Rosc, Phyllanthus emblica, and salicylic acid, was developed for acne vulgaris. These natural raw materials were blended with suitable dosages of gelatin and carboxymethyl cellulose (CMC) to produce a biocompatible herbal gel. The physical chemistry properties of the hydrogel were determined by Fourier transform infrared spectroscopy (FTIR), thermal gravimetric analysis (TGA), rheometry, and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“… 23 Oxidative stress is often accompanied by pro‐inflammatory cytokine expression. 24 , 25 qPCR assays of interleukin 6 ( Il6 ) and tumor necrosis factor α ( Tnfα ) were performed in each group of cells. The four groups of cells were collected and subjected to RNA extraction for qPCR assays.…”
Section: Resultsmentioning
confidence: 99%
“… 23 Oxidative stress is often accompanied by pro‐inflammatory cytokine expression. 24 , 25 qPCR assays of interleukin 6 ( Il6 ) and tumor necrosis factor α ( Tnfα ) were performed in each group of cells. The four groups of cells were collected and subjected to RNA extraction for qPCR assays.…”
Section: Resultsmentioning
confidence: 99%
“…For two reasons, an acidic pH is essential for barrier homeostasis: first, two ceramide-synthesizing enzymes have low pH optima; and second, a low pH promotes the 13-nm long periodicity phase required for barrier construction. An acidic pH, in other words, generates a more effective barrier [26,29,31]. A lower skin surface pH is associated with greater resistance to SLS-induced irritating dermatitis, whereas patients with skin pH 5 have less scaling and higher moisture levels than those with skin pH > 5 [28,30].…”
Section: Resultsmentioning
confidence: 99%
“…After seven days of using herbal sunscreens, a skin irritation study found no irritation, sensitivity, or minor or patchy erythema (Table 2) [31].…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Research on PE extract has demonstrated its potential utility in natural healthcare products, such as food, health, and cosmetic products [47,48]. There is some evidence that suggests PE extract can have a positive impact on the skin, such as anti-aging, skin whitening and antioxidant properties [47,49,50]. However, more research is needed to fully understand the effects of PE extract on the skin and its optimal use as a topical treatment.…”
Section: Discussionmentioning
confidence: 99%